Avaliação diferencial de fatores fisiológicos e cinéticos em cultivos de linhagens de células selvagem e recombinante de Drosophila melanogaster S2 - Silva, Clóvis Sacardo da (Universidade Federal de São Carlos, 2005)
In the last 10 years the insect cell Drosophila melanogaster Schneider S2 has been increasingly used for studies of proteins recombinants. However, there is a lack of studies that involved parameters related to the use of the insect cell Drosophila melanogaster in bioprocess. The aim of this work was to study the factors physiologies important in the cultures of the insect cells Drosophila melanogaster S2 (S2) and recombinant S2 (rS2), through cultures in Schott flask, serum free medium at 28°C. There were performed experiments with the purpose of monitoring the viability cellular of insect cells by the methods of exclusion of Trypan blue and of fluorescent dyes. Both methods used in the experiments to monitor the viability of the cultures of the cells S2 and rS2 were shown reliable for the identification of the percentage of viable cells. The studies revealed that growth of S2 and rS2 cells was not limited by the total consumption of amino acids and glucose. In the experiments utilizing the rS2 cells to verify the influence of the age of the inoculum and concentration of the inoculum, it was verified that both parameters did not have influence in the growth specific rate. Experiments done in Schott flask of 250 mL with a working of 50 mL, in which were monitored the concentration of dissolved oxygen (DO) in the broths of cultivation of the cells S2 and rS2. The results demonstrated that the cultivation reaches the stationary phase with very low level of dissolved oxygen, whit DO being a limiting factor of the growth of the cells. The specific oxygen consumption rate (QO2) demonstrates an accentuated decrease in the exponential phase of growth, except for stationary phase. The excess of oxygen in the initial phase of the cultivation was harmful to the growth of the cells. However, in the experiments done in Schott flask 100 mL with a working volume of 20 mL, QO2 of the cells rS2, revealed 10 to 15 times smaller than these performed in the Schott flask of 250 mL. The experiments done in Schott flask of 100 mL with different agitations demonstrated that for low agitation the transfer of oxygen should be a limiting factor in the cellular growth. The cellular viability for all of the experiments performed in different agitations stayed between 95 and 99% of viable cells indicating that the cells were in good physiologic state.
Keywords: Engenharia bioquímica; Drosophila melanogaster; Aminoácidos; Apoptose; Velocidade específica de respiração; ENGENHARIAS::ENGENHARIA QUIMICA